2021
DOI: 10.3390/ijms222111528
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Neural Probes with Electrochemical Modified Microelectrodes for Artifact-Free Optogenetic Applications

Abstract: With the rapid increase in the use of optogenetics to investigate nervous systems, there is high demand for neural interfaces that can simultaneously perform optical stimulation and electrophysiological recording. However, high-magnitude stimulation artifacts have prevented experiments from being conducted at a desirably high temporal resolution. Here, a flexible polyimide-based neural probe with polyethylene glycol (PEG) packaged optical fiber and Pt-Black/PEDOT-GO (graphene oxide doped poly(3,4-ethylene-diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To minimize the effect of optoelectronic artifacts, highly transparent materials such as graphene [ 52 ] or indium tin oxide [ 105 ] have been used as electrode materials. Flexible polymer-based substrates to eliminate PV-induced artifacts are also a good option [ 106 , 107 , 108 ].…”
Section: Optoprobesmentioning
confidence: 99%
“…To minimize the effect of optoelectronic artifacts, highly transparent materials such as graphene [ 52 ] or indium tin oxide [ 105 ] have been used as electrode materials. Flexible polymer-based substrates to eliminate PV-induced artifacts are also a good option [ 106 , 107 , 108 ].…”
Section: Optoprobesmentioning
confidence: 99%
“…To measure the accuracy of predicted DF as an absolute or quantitative value, we calculated the difference between the last value of the actual DF signal and the last value of the predicted one. Then, we normalized it to the maximum range of the actual DF, which gave us the relative error of the predicted signal; thus, (1-error) expresses the accuracy of the equality between the actual and the predicted DF as shown in Equation (3).…”
Section: Accuracy Of Final State (Afs)mentioning
confidence: 99%
“…The primary goal of biointerface technology is the understanding of interactions between biomolecules and corresponding surfaces or mediums, which has recently been considered significant in the fields of biology, biotechnology, diagnostics, and medicine [2]. Biointerface technology has widespread applications, for example, but not limited to, neural interfaces that deal with the nervous system for recording and stimulating purposes [3], pathogenesis and pathogen detection [4], membrane-based biosensing [5], nanotube/nanoparticle interfaces and cells in engineered microenvironments, and regenerative medicine [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the PEC noise (up to 200 µVpp) on the metal-electrolyte interface can be mitigated by using electrochemical modification of materials with a band gap of larger than 3.26 eV, such as counterion-doped PEDOT, Sn-doped indium oxide or graphene [24,25]. In a previously published work [26], it was demonstrated that graphene oxide-doped PEDOT (PEDOT-GO) can effectively reduce PEC noise. However, direct comparison of electrochemical performance, stability and PEC noise of the PEDOT-GO modifications with the PEDOT-PSS modifications has not been reported.…”
Section: Introductionmentioning
confidence: 99%